An analysis of the role played by translation in minority languages: Welsh and Breton compared - Robert Neal Baxter (Quaderns)
There is general agreement in the burgeoning literature on the subject that translation plays a key role in minority languages, fulfilling a variety of functions, including bolstering the literary canon. This leads to a prevalent assumption that this veritable entails a dependence on translation that renders minority languages ‘weak’. Following a theoretical review of the literature and a brief presentation of the languages, this paper discusses the results of a study based on a broad-based, original dataset representative of the wide range of literature currently available in Breton and Welsh. The paper concludes that a portrayal of minority language literary systems as ‘weak’ is overly simplistic and fails to address and attempt to explain the factors underpinning the complex and often contradictory dynamics played by translation both within and between such languages.